Ceilings and dreams : the architecture of levity - Emmons, Paul; Goffi, Federica; La Coe, Jodi (New York : Routledge, 2019)
Where is the space for dreaming in the twenty-first century? Lofty thoughts, like dreams, are born and live overhead, just as they have been represented in Renaissance paintings and modern cartoons. Ceilings are often repositories of stories, events and otherwise invisible oneiric narratives. Yet environments that inspire innovative thinking are dwindling as our world confronts enormous challenges, and almost all of our thinking, debating and decision-making takes place under endless ceiling grids. Quantitative research establishes that spaces with taller ceilings elicit broader, more creative thoughts. Today, ceilings are usually squat conduits of technology: they have become the blind spot of modern architecture. The twenty essays in this book look across cultures, places and ceilings over time to discover their potential to uplift the human spirit. Not just one building element among many, the ceiling is a key to unlock the architectural imagination. Ceilings and Dreams aims to correct this blind spot and encourages architects and designers, researchers and students, to look up through writings organized into three expansive categories: reveries, suspensions and inversions. The contributors contemplate the architecture of levity and the potential of the ceiling, once again, as a place for dreaming.
From Below Upwards : An Introduction to Ceilings and Dreams / Paul Emmons -- Storywork. Henry Chapman Mercer's Cast-in-Place Tile Vaults and the Invention of Practice / Luc Phinney -- Looking down to Look up / Marcia F. Feuerstein.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Ceilings; Architecture -- Psychological aspects; ARCHITECTURE / General; ARCHITECTURE / History